(untitled) (Jurnal Adabiya, 2025)
Local libraries must innovate in developing digital collection services. This study aims to evaluate the user interface and user experience of the iLamongan application based on Dmitry Fedeyev’s theory. Researchers used a descriptive qualitative approach. Data search techniques with observation, interviews, and documentation. Data analysis through the process of reduction, presentation, and conclusion drawing. Test validity with triangulation techniques. The results showed that the user interface in the iLamongan application had fulfilled six of the eight aspects. User experience assesses that the presence of iLamongan provides innovation for users who are unable to attend directly to the library. Users still experience technical obstacles such as signal stability and eye endurance when reading for a long time. Feature updates need to pay attention to user needs, such as the absence of light dark mode, reading models, and others. The iLamongan app has fulfilled many aspects of a good UI and provides a positive user experience. However, there is still room for improvement especially in the aspects of efficiency and completeness of the collection. This evaluation is important for further development so that the application can meet user needs. ABSTRAK Perpustakaan daerah harus melakukan inovasi pengembangan layanan koleksi secara digital. Penelitian ini bertujuan menganalisis user interface dan user experience pada aplikasi iLamongan berdasarkan teori Dmitry Fedeyev. Peneliti menggunakan pendekatan kualitatif deskriptif. Teknik pencarian data dengan observasi, wawancara, dan dokumentasi. Analisis data melalui proses reduksi, penyajian, dan penarikan kesimpulan. Uji keabsahan dengan triangulasi teknik. Hasil penelitian menunjukan user interface pada aplikasi iLamongan sudah terpenuhi enam dari delapan aspek. User experience menilai hadirnya iLamongan memberikan inovasi bagi pengguna yang berhalangan hadir langsung ke perpustakaan. Kendala teknis pengguna masih dialami seperti stabilitas sinyal dan daya tahan mata ketika membaca lama. Pembaruan fitur perlu memperhatikan kebutuhan pengguna, seperti belum adanya mode gelap terang, model baca, dan lainnya. Aplikasi iLamongan telah memenuhi banyak aspek UI yang baik dan memberikan pengalaman pengguna yang positif. Namun, masih ada ruang untuk perbaikan terutama dalam aspek efisiensi dan kelengkapan koleksi. Evaluasi ini penting untuk pengembangan lebih lanjut agar aplikasi dapat memenuhi kebutuhan pengguna.